2022
DOI: 10.26434/chemrxiv-2022-vts5z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual-Band Electrochromism: Plasmonic and Polaronic Mechanisms

Abstract: Electrochromic windows that dynamically absorb incident solar irradiation are envisioned as smart technology devices that can reduce power consumption in buildings and accelerate progress toward sustainable development. While regulating the visible light in interior spaces to suite the comfort of occupants, electrochromic windows also offer thermal control by controlling the flux of solar energy, including infrared radiation. The ability to selectively modulate visible and the infrared solar transmittance is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This stable electrochemical cycling with a polaronic mechanism is more likely to avoid rapid microstructural degradation. 50,51 It is concluded that the FA cast films possess a more stable microstructure, resulting in enhanced polaron stability, which is further reflected in the operational stability of the devices.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
See 1 more Smart Citation
“…This stable electrochemical cycling with a polaronic mechanism is more likely to avoid rapid microstructural degradation. 50,51 It is concluded that the FA cast films possess a more stable microstructure, resulting in enhanced polaron stability, which is further reflected in the operational stability of the devices.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…The difference in the film microstructure brings about a significant difference in the spectral response of the polaronic materials. 50 To analyze the polaron stability of gNR, we monitor the changes in the intensity of the polaron absorption peak of four cast films with alternating biased potentials ranging from −0.3 to 0.2 V in a 0.1 M NaCl aqueous solution for 10 cycles. As shown in Figure S11, a large drop in the normalized absorbance of 52% (the tenth scan) is observed for gNR-CF.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Coloration efficiency (CE) is an important parameter to evaluate the EC performance, which is defined as the change in optical density (OD) at a selected wavelength caused by the injection or extraction of electric charge into the DESW per unit area. 23,24 The definition formula is as follows:…”
Section: Optical Contrastmentioning
confidence: 99%
“…While in the process of polaronic electrochromism, electrons and ions need to be intercalated and deintercalated from the NC host and the diffusion speed and distance of ions in the host may affect its switching speed. 24 Increasing the specific surface of NCs, reducing the diffusion path of ions, and increasing the diffusion rate of ions have become important methods to accelerate the EC process of polarons.…”
Section: Response Timementioning
confidence: 99%